Collapse-Pounding Dynamic Responses of Adjacent Frame Structures under Earthquake Action - Wei Jing; Shangshang Xing; Yu Song (Advances in Civil Engineering)
There are a large number of adjacent buildings in practical engineering application. The structure will collapse and impact the adjacent structures once the weak column is destroyed under seismic action, and, finally, the earthquake damage is aggravated. Material nonlinearity, initial imperfections, and contact problems in the process of collapse-pounding are considered, and the three-dimensional calculation model with unequal 8-story and 6-story height adjacent frames is established. The dynamic response of adjacent structures caused by collapse-pounding is investigated when there is a weak column at different positions in the 8-story frame, and the influence of gap size on the dynamic responses of adjacent structures is discussed. The results show that the impact force is larger when the weak column of the 8-story frame is close to the top of the 6-story frame; pounding increases the interlayer displacement angle of the 8-story frame and decreases the interlayer displacement angle of the 6-story frame in general; the impact force decreases first, then increases, and after that decreases with the increase of gap size; and the interlayer displacement angle distribution of the 6-story frame is significantly affected after the collapse-pounding of the 8-story frame with a weak column. The collapse-pounding problem of adjacent buildings under seismic action is very complex, which should be paid enough attention in engineering design and application.